Sistem Informasi Penilaian Kinerja Perawat pada Rumah Sakit Husada Utama Surabaya - rohim, mohammad syahadatul; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi Universitas Dinamika, 2020)
The nurse performance appraisal process begins with the HR unit sending an internal memo notifying the nurse performance appraisal to each unit (1 day). The head of the unit who has received an internal memo then evaluates the nurse's performance by filling in the assessment form (20 days). After completing the assessment, the head of the unit submits the assessment form to the HR unit, then the HR unit will do the calculation and report making (3 days). The problem at the moment is first, the collection of the assessment form is late because the Head of the Unit has a need outside the hospital or is receiving training, consequently causing a delay in calculation time, and the impact of the HR Unit being late in making a report. Second, calculations that require 3 days or more can be due to the large number of forms that have to be processed, calculation errors often occur, as a result it affects the incorrect assessment results, and accurate, the impact can slow down the preparation of reports. Third, the search file evaluation of nurses takes a long time because it takes from the storage shelves one by one, as a result the HR Unit requires a long time in looking for the value of the nurse, the impact of inefficient time in searching the file to see the performance of nurses perperiod. The results of trials that have been carried out show that this application can complete the process of collecting late assessment forms, calculations that require 3 days or even more, and searching for nurse assessment files requires a long time. The HR unit is assisted in the monitoring process by displaying nurse assessment information in the form of periodic charts.